2018
DOI: 10.1080/02670844.2017.1327009
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Ni–Mo and Ni–Mo-(nano Al2O3) multilayer coatings

Abstract: In the present work, multilayer Ni-Mo-Al 2 O 3 and Ni-Mo coatings were fabricated on the lowcarbon steel using pulse electrodeposition technique from a citrate-ammonia bath. The coatings with different number of layers (32, 128 and 512) were electrodeposited by the periodic alteration of duty cycle (between 20 and 90%) at a constant frequency of 400 Hz and an average current density of 6 A dm −2 . The corrosion resistance of the coatings was estimated using potentiodynamic polarisation and electrochemical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Rezaeiolum et al [42] reported that the morphology of Ni-Mo coatings depends on the bath concentration. The surface of the coating shown in Figure 5A, obtained from experiment 2, at a NiSO 4 to Na 2 MoO 4 concentration ratio of 1:1 , is heterogeneous from the morphological point of view.…”
Section: Electrodeposition and Chemical Compositionmentioning
confidence: 99%
“…Rezaeiolum et al [42] reported that the morphology of Ni-Mo coatings depends on the bath concentration. The surface of the coating shown in Figure 5A, obtained from experiment 2, at a NiSO 4 to Na 2 MoO 4 concentration ratio of 1:1 , is heterogeneous from the morphological point of view.…”
Section: Electrodeposition and Chemical Compositionmentioning
confidence: 99%
“…This gradient-layered structure of coating acts as a barrier along with nanoparticles and prevent the rapid diffusion of corrosive ions towards the substrate. Moreover, the existence of more complex and longer corrosion paths improves the corrosion resistance due to the presence of nanoparticles [57][58][59]. The presence of alumina enhances corrosion resistance and E corr is shifted towards more positive values.…”
Section: Microstructure and Chemical Composition Of The Coatingsmentioning
confidence: 99%
“…Ni-based alloys are widely used cathodes for the electrolysis of alkaline waters due to the relatively high catalytic activity of Ni, and the synergism in the catalytic behavior of various components in the metal alloy. Alloys such as NiCo [35][36][37][38][39][40][41], NiFe [42][43][44][45][46], NiMo [43,[47][48][49][50][51][52][53][54][55][56][57][58][59], NiW [47,60,61], NiCu [62,63], NiAl [6,[64][65][66][67][68], NiZn [69][70][71][72][73], NiMoFe [56,[74][75][76][77] were used by means of different methods. Materials based on nickel and molybdenum attract ever growing attention because of their activity for HER and sufficient corrosion resistance in...…”
Section: Chemical Problems 2018 No 3 (16)mentioning
confidence: 99%